Bibliometrics : use and abuse in the humanities - Žic Fuchs, Milena (Array, 2014)
Decades of repeated attempts, throughout European Humanities communities, to evaluate Humanities research on the basis of databases such as WoS, SCOPUS, etc. have proven unsuccessful for a number of reasons, but primarily because of the specific nature of research in the Humanities primarily reflected in specific outputs. This is particularly reflected in the distinction between metrics led and metrics informed evaluation, as well as their relationship to peer judgment. The role of ERIH (the European Reference Index in the Humanities) is discussed in this regard, as well as the role it has played, both as a visibility and an evaluation tool in Europe since the initial publication of lists in 2007. New developments, new databases, and possible new approaches to the evaluation of the Humanities outputs is discussed, as well as new trends in bibliometrics in other domains of research apart from the Humanities.